Prevalance of Hpv Infection in Women Living with HIV Attending Waibargi Specialist Hospital (London Journal of Medical and Health Research, 2025)
Cervical cancer remains a significant public health concern, particularly for women living with HIV (WLWH), due to their increased susceptibility to persistent human papillomavirus (HPV) infections. This study aims to assess the prevalence of high-risk HPV (hrHPV) infections in WLWH attending Waibargi Specialist Hospital in Myanmar in the year 2024. The cross-sectional analysis involved 234 WLWH, tested with Cobas 4800 system HPV DNA test. Colposcopy directed biopsies were conducted among the participants to detect the presence of cervical intraepithelial neoplasia (CIN) and invasive carcinoma.The results revealed a high HPV prevalence of 29.9% among the study population, with 70 women tested positive for one or more high-risk HPV types.  Among those, single infection with HPV 16 was found in 9 women (3.8%), HPV 18 in 8 (3.4%) while 35 (15%) of them were infected with other high-risk HPV types. Additionally, 18 women (7.7%) had mixed infections involving multiple hrHPV types.  The study also identified that women on ART for more than three years exhibited significantly lower HPV infection rates, as did those with undetectable viral loads, suggesting that effective HIV management can mitigate HPV-related cervical cancer risk.In this study, 41 women (70.7%) out of 58 HPV-positive cohort diagnosed with CIN I or more severe histological abnormalities after colposcopy directed biopsy. Notably, 86.7% of patients with HPV 16, 18, or mixed infections had positive histology results, compared to 53.6% in those with other hrHPV.In conclusion, this study highlights the high prevalence of hrHPV infections and the association between specific HPV genotypes and the development of cervical pre cancer and cancer among WLWH. The study also emphasizes the need for integrated cervical cancer screening and vaccination programs within HIV frameworks along with the importance of proper HIV treatment. However, since it is a hospital-based study, further research is required to cover the broader populations, particularly in rural and underserved areas of Myanmar.
Keywords: Quality improvement; brazil; organ transplantation; management program; PAT-MA; health systems; Maranh; pulmonary hypertension.; Chronic thromboembolic pulmonary hypertension; Thrombendarterectomy; Pulmonary vascular resistance; Long-term medical history.; HIV; cervical cancer; Screening; CIN; HPV